FxD: a functional debugger for dysfunctional spreadsheets - Drosos, Ian; Wilson, Nicholas; Gordon, Andrew D.; Ragavan, Sruti Srinivasa; Williams, Jack (Proceedings (IEEE Symposium on Visual Languages and Human-Centric Computing), 2023)
Recent enhancements to the spreadsheet formula language and intelligent spreadsheet interfaces allow spreadsheet users to build more complex spreadsheets in systematic ways (e.g., via functional abstractions). However, users have been slow to adopt such features, partly due to the absence of corresponding improvements in tools such as editors and debuggers. In this paper, we present FxD, a novel spreadsheet debugging interface, which provides structured information needed for spreadsheet users to debug formulas in systematic ways through affordances such as the ability to step into the execution of dependencies and provide contextual information to users based on the current context. An in-vitro, within-subject (n=12) experiment revealed that, even though using FxD did not lead to faster debugging, participants reported qualitative improvements (e.g., feelings of efficiency and capability) when debugging with it. Further, participants were more satisfied with the amount of information provided by FxD and felt that it would enhance their existing debugging workflows. Our results have implications for the design of debuggers for spreadsheets and for functional programming languages in general.